2014
DOI: 10.1021/jp504254a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Side-Chain-Induced Disorder on the Emission Spectra and Quantum Yields of Oligothiophene Nanoaggregates: A Combined Experimental and MD-TDDFT Study

Abstract: Oligomeric thiophenes are commonly used components in organic electronics and solar cells. These molecules stack and/or aggregate readily under the processing conditions used to form thin films for these applications, significantly altering their optical and charge-transport properties. To determine how these effects depend on the substitution pattern of the thiophene main chains, nanoaggregates of three sexithiophene oligomers having different alkyl substitution patterns were formed using solvent-poisoning te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…The amorphous features of these carbazole compounds are very much disadvantageous to grow a single crystal to study the molecular packing. However, with support from the literature, 815 we speculate that the carbazole ring is considerably twisted for both the compounds. To support our speculation, the molecular structure of compound 3b is optimized using DFT (density functional theory) studies where the carbazole ring is twisted almost 80° with the anthracenyl core (Figure 4).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The amorphous features of these carbazole compounds are very much disadvantageous to grow a single crystal to study the molecular packing. However, with support from the literature, 815 we speculate that the carbazole ring is considerably twisted for both the compounds. To support our speculation, the molecular structure of compound 3b is optimized using DFT (density functional theory) studies where the carbazole ring is twisted almost 80° with the anthracenyl core (Figure 4).…”
Section: Resultssupporting
confidence: 78%
“…14 Thus, the aggregation-caused quenching (ACQ) property of anthracene was detrimental to execute real-world applications. 15 Later, aggregation-induced emission (AIE) for anthranyl compounds was detected mainly for distyrylanthracene (DSA) derivatives. 16 Also, much smaller anthracene-based AIEgens were reported by us.…”
Section: Introductionmentioning
confidence: 99%
“…Organic nanoparticles have attracted significant research interests for their promising potential applications in nanoscale optoelectronic devices owing to their unique luminescent properties, such as nanoparticle size-tunable optical property, 1 multicolor emissions, 2 excitation wavelength-dependent multiple emissions, 3 and so on. 4 Recently, a newly prepared αsexithiophene (α6T) nanoparticle with a diameter range from 100 to 200 nm was found to exhibit a blue shift in both absorption and emission spectra compared to the solution, 5 which is quite different from the previous reported red shift in emission upon aggregate in crystal, 6 thin film, 7 and nanoaggregates. 8,9 Understanding the luminescent mechanism of the organic nanoparticle is of great importance for designing and achieving excellent organic opto-functional nanomaterials.…”
Section: Introductionmentioning
confidence: 74%
“…15 Through molecular dynamics (MD) simulation and time-dependent density functional theory (TDDFT) calculations, Ma et al claimed that the blue shift in absorption of α6T nanoparticle results from the formation of the high-energy distorted chains. 5,16 Using the multimode-coupled spectral theory of an isolated molecule and combined MD simulations and quantum mechanics/molecular mechanics (QM/MM) calculations, Shuai et al explored the relationship among molecular packing, optical spectra, and fluorescence quantum efficiency of hexaphenylsilole nanoparticles and revealed that the decreased reorganization energy results in the blue shift of the emission spectra from amorphous to crystalline phases. 17 Gierschner et al treated the vibronic coupling in the molecular crystal based on pure quantum chemical cluster calculations.…”
Section: Introductionmentioning
confidence: 99%
“…COs have also been used to fabricate aggregates to probe morphology and spectroscopic information at nanoscale by the Peteanu group. 52 , 53 …”
Section: From Single Molecules To Aggregatesmentioning
confidence: 99%